Collecting villagers perspectives in the Mekong Delta - Ly Duc Tai; Pham Quynh Trang (Technical Centre for Agricultural and Rural Cooperation, 2018)
The Mekong Delta is a highly productive agricultural area and is vital to global food security, the Vietnamese economy and for sustaining the livelihoods of its 18 million residents. While the production of rice dominates agriculture in the Delta as a whole, some areas within it are well known for unique food products such as the fish coming from the flooded areas, the fruit from the middle alluvial area and the shrimps from the coast. The whole area, however, has changed drastically in the past twenty years. The project called “River food systems from villagers’ perspectives in the Mekong Delta”, implemented by WARECOD, a Vietnamese NGO and its partners, ran between 2015 and 2016. The team gathered local knowledge and conducted scientific research, looking in detail at the impact of the irrigation systems built since 2000 and at the changes they have brought.